COMPARATIVE EFFICACY OF LONG-TERM ANTIHYPERTENSIVE MONOTHERAPY IN PATIENTS WITH ARTERIAL HYPERTENSION AT THE WORK PLACE - О. N. Antropova; I. V. Osipova; E. I. Kuznetzova; N. V. Piricova; I. I. Curbatova (Рациональная фармакотерапия в кардиологии)
Aim. To compare effects of 12-month monotherapy with nebivolol, enalapril and indapamide on blood pressure (BP), left ventricular hypertrophy and quality of life in the locomotive engineers and their assistants with stress-associated hypertension at the work place (HTwp).Material and methods. 96 locomotive engineers (20- 53 y.o) and their assistants with HTwp were observed. The patients were randomized to receive nebivolol (1 group), enalapril (2 group) or indapamide (3 group). 24-hour BP monitoring, echocardiography and quality of life interview with SF–36 questionnaire were performed at the start and after 12 months of the treatment.Results. Long-term therapy lead to achievement of target BP level, improved quality of life and reduced in left ventricular hypertrophy in patients with HTwp. Nebivolol reduced systolic “BP load” more significantly than indapamide did, exerted favorable influence on circadian BP rhythm and reduced heart rate. Monotherapy with nebivolol showed benefits in effect on quality of life.Conclusion. Nebivolol has some advantages in comparison with indapamide and enalapril in antihypertensive therapy of patients with stress-associated HT.